Workplace Violence in Workers with Multi-Party Employment Arrangements: Results from the Korean National Representative Survey - Yeogyeong Yoon; Kyunghee Jung-Choi (Safety and Health at Work, 2022)
Background: Despite a growing number of investigations exploring the health problems in precarious workers, there is still a paucity of studies investigating workplace violence in workers with multi-party employment arrangements (WMPEAs). This study was aimed at comparing the prevalence of workplace violence between non-WMPEA and WMPEA. Methods: The 5th Korean Working Conditions Survey data were used. The study subjects were employees aged 20-74, with 26,239 non-WMPEA and 1,556 WMPEA. WMPEA included temporary agency workers and workers providing outsourced services. Workplace violence including verbal abuse, unwanted sexual attention, threats, and humiliating behaviors were used as outcome variables. The odds ratios of risk of workplace violence were calculated using multiple logistic regression. Results: The age-standardized prevalence of workplace violence was significantly higher among WMPEA. After adjusting for all covariates, the risk of workplace violence among WMPEA was still significant (OR 1.80, 95% CI 1.5-2.2) compared with non-WMPEA. The odds ratio of workplace violence among female WMPEA was 1.99 (95% CI 1.53-2.59), which is higher than that of male WMPEA (OR 1.52, 95% CI 1.18-1.96). Conclusion: We found that WMPEA were exposed to higher risk of workplace violence. Discrimination against WMPEA in the working environment and management policy need to be corrected. It is also necessary to identify the risk factors of workplace violence in WMPEA and to make efforts to prevent violence.